Environmental Uncertainty Factor, Incoterm and Implication For A Strategic Alliance In Freight Forwarder Companies Case Study In Indonesia - Sugiono, Ahmad; Rahayu, Agus; Wibowo, Lili Adi (Asian Journal of Logistics Management, 2022)
The study analyzes the effect of environmental uncertainty and incoterms on strategic alliances. The population in this study is a freight forwarder company on the island of Java that has a global alliance. The research sample is 50 companies engaged in international freight forwarders. Based on answers from respondents were analyzed according to the research model developed from the theoretical framework using the structural equation model Smart-PLS approach. The analysis results show that environmental uncertainty and Incoterm positively and significantly affect strategic alliances. The alliance strategy will impact when the main priority is the risk-sharing aspect, the risk management factor from the incoterm aspect, and the market turbulence on the environmental uncertainty factor. Novelty in this study is the positive impact of Incoterm on the alliance strategy, especially for International freight forwarders. This research contributes to the factors considered in strategic alliances in the freight forwarder industry. It also contributes to the company's strategy, especially sales managers, to pay attention to international trade terms in segmenting and selecting target consumers to be more effective in improving alliance performance. The limitations of this study include 1) The sample size used is only a small number of companies engaged in international Freight Forwarder services, only 50 companies; 2) The data used in this research is through the distribution of questionnaires based on perceptual analysis units; 3) Other factors that are outside the model are not all studied, while the possibility of these factors can affect the existing significance test.